The Philosophy of Ethics and Humanitarian Crises: The Gaza War as a Case Study of International Humanitarian Dimensions (مجلة دراسات إقلیمیة, 2026)
Research Idea: This research examines the fundamental relationship between moral philosophy and humanitarian crises in the international context by analyzing how ethical frameworks shape the international community’s response to such crises. It is grounded in the central question of whether contemporary ethical thought is capable of aaddressing the challenges posed by humanitarian crises. The study highlights the gap between proclaimed moral principles and actual practice, underscoring the need for a philosophical reassessment of ethical concepts, particularly regarding collective responsibility toward vulnerable populations. The Gaza War serves as a case study for examining this issue.Objective: The research aims to evaluate the effectiveness of moral philosophy in interpreting and assessing the international community’s response to humanitarian crises through the case of Gaza, which reveals contemporary ethical challenges.Methodology: The research employs multiple approaches, including analytical methods to deconstruct key concepts, comparative analysis to examine patterns of international behavior, and a case-study approach to test ethical concepts in practice.Results: The findings indicate that realist theory explains the instability of the international system and the predominance of national interests over ethical values. The Gaza War exposed violations and double standards that reinforce future conflict narratives. Historical examples further demonstrate that power alone is insufficient to resolve crises and that states that disregard ethical considerations may achieve short-term gains but risk losing international legitimacy and undermining their own security.Conclusion: The research concludes that ethics is not a secondary consideration but a necessity in international politics. Combining realism with ethical principles offers the most effective path toward a more just and stable international order. International legitimacy is closely linked to ethical commitment, while sustainable peace requires leadership that balances interests with justice. The Gaza tragedy also highlights the need for effective international pressure to secure Palestinian rights and for the development of a binding global ethical charter that affirms equality in human dignity.